1997
DOI: 10.1095/biolreprod56.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Promoter Region of the Rat Testis-Specific Histone H1t Gene1

Abstract: Histone H1t is synthesized only in male germ cells during the late pachytene stage of meiosis and is retained in spermatids until the nucleus elongates. Transgenic experiments suggest that spermatocyte-directing sequences lie within 140 base pairs of the cap site. To study the mechanism of this specificity we compared the DNase I footprints made on the immediate promoter regions of H1t and H1d (a typical somatic H1) by testis and liver extracts and observed both common and differentially protected regions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…As described above (8) spermatidspecific transcription of mouse protamine 1 is induced by a 113 bp region from Ϫ150 to Ϫ37. For rat histone H1t gene, studies in transgenic mice revealed that the region from Ϫ141 to ϩ70 was sufficient to confer spermatocyte-specific expression of the gene (19). Thus, our data confirm the observation that genes with male germ cell specific expression tend be regulated by very small promotor regions.…”
Section: Figsupporting
confidence: 86%
“…As described above (8) spermatidspecific transcription of mouse protamine 1 is induced by a 113 bp region from Ϫ150 to Ϫ37. For rat histone H1t gene, studies in transgenic mice revealed that the region from Ϫ141 to ϩ70 was sufficient to confer spermatocyte-specific expression of the gene (19). Thus, our data confirm the observation that genes with male germ cell specific expression tend be regulated by very small promotor regions.…”
Section: Figsupporting
confidence: 86%
“…In our earlier investigation, comparison of the H1t and H1d promoters by in vitro transcription did not demonstrate consistent differences using liver or testis extracts (39). We do not know why the strong inhibitory effect of H1t GC box 2 seen with transient transfections was not observed with in vitro transcription.…”
Section: Activating Effect Of Gc Box 1 Demonstrated In the Context Ofmentioning
confidence: 74%
“…Promoter-An earlier study of the H1t promoter demonstrated that GC box 1 is a good binding site for Sp1-like factors, and a strong stimulatory site for in vitro transcription (39). Since GC box 2 is shown here to be an inhibitory site, we reinvestigated the activating role of GC box 1 in the context of a mutation that relieved inhibition at GC box 2.…”
Section: Activating Effect Of Gc Box 1 Demonstrated In the Context Ofmentioning
confidence: 99%
See 2 more Smart Citations